INTERACTIVE AI BASED DICTIONARIES: NEW HORIZONS IN LEXICOGRAPHY AND LANGUAGE LEARNING - Khalilova Maftuna Azamat qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
This article explores the extensive capabilities of artificial intelligence (AI)-based interactive dictionaries in enhancing vocabulary learning and lexicography. It discusses various AI applications, including chatbots, gamification, virtual and augmented reality, corpus linguistics, and social media platforms, which collectively contribute to a more engaging and effective language acquisition process. The integration of AI technologies enables real-time interaction, contextual understanding, pronunciation assistance, and error correction, thus offering personalized learning experiences.